Suicide behavior and anxiety among users of a psychosocial care center in northeast Brazil - Santos, Bruno Andrade (2021)
Suicidal behavior has been conceptualized as a continuum of thoughts and behaviors from ideation to suicide itself. This article aimed to analyze the prevalence and the factors associated with suicidal behavior and the level of anxiety among users of a Psychosocial Care Center (CAPS). This is an observational and cross-sectional study conducted between July and September 2019 with 188 adult users of a CAPS in Lagarto, Sergipe. The Beck Anxiety Inventory and the Columbia-Suicide Severity Rating Scale were used. The results showed that, during life, the prevalence of suicidal ideation was 52.7% and suicide rates, 31.8%, being higher among people who had a family income lower than a minimum wage (PR: 1.36, 95% CI: 1.07-1.56; PR: 1.97, 95% CI: 1.19-2.70, respectively). Regarding anxiety, 27.7% moderate anxiety and 21.8%, severe. Severe anxiety and effective suicide attempt were more prevalent in females (PR: 2.70, 95% CI: 1.23-2.83; PR: 1.74, 95% CI: 1.23-1.84, respectively). Effective suicide attempt is associated with severe anxiety (PR: 2.99, 95% CI: 2.08-5.19). High prevalence and interrelations of suicidal ideation, effective suicide attempt, and severe anxiety among users were found, with the influence of gender and family income.